From Manual Tracing to Machine Learning: The Definitive Comparison of AI and Traditional Public Health Surveillance - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Effective public health relies on surveillance—the continuous, systematic collection, analysis, and interpretation of health-related data 1. For decades, thi...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine; Machine Learning